Development and validation of brain-derived neurotrophic factor measurement in human urine samples as a non-invasive effect biomarker - Olivas-Martinez, Alicia; Suarez, Beatriz; Salamanca-Fernandez, Elena; Reina-Perez, Iris; Rodriguez-Carrillo, Andrea; Mustieles, Vicente; Olea, Nicolás; Freire, Carmen; Fernández, Mariana F. (Frontiers in Molecular Neuroscience, 2023)
Background: Brain-derived neurotrophic factor (BDNF), a neurotrophic growth factor mainly expressed in the brain, has been proposed as a potential effect biomarker; that is, as a measurable biomarker whose values could be associated with several diseases, including neurological impairments. The European Human Biomonitoring Initiative (HBM4EU) has also recognized effect biomarkers as a useful tool for establishing link between exposure to environmental pollutants and human health. Despite the well-establish protocol for measuring serum BDNF, there is a need to validate its assessment in urine, a non-invasive sample that can be easily repeated over time. The aim of this study was to develop, standardize and validate a methodology to quantify BDNF protein levels in urine samples before its implementation in biomonitoring studies. Methods: Different experimental conditions and non-competitive commercial enzyme-linked immunosorbent assay (ELISA) kits were tested to determine the optimal analytical procedure, trying to minimize the shortcomings of ELISA kits. The fine-tune protocol was validated in a pilot study using both upon awakening (n=150) and prior to sleeping (n=106) urine samples from the same Spanish adolescent males in a well-characterised study population (the Spanish INMA-Granada cohort). Results: The best results were obtained in 0.6 mL of urine after the acidification and extraction (pre-concentration) of samples. The highest reproducibility was obtained with the ELISA kit from Raybiotech. Urinary BDNF concentrations of adolescent males were within the previously reported range (morning= 0.047-6.801 ng/mL and night= 0.047-7.404 ng/mL). Urinary BDNF levels in the awakening and pre-sleep samples did not follow a normal distribution and were not correlated. Conclusion: The developed methodology offers good sensitivity and reproducibility. Having reliable markers in urine may facilitate both diagnosis and monitoring possible diseases (and treatment). Further studies are needed to implement urinary BDNF in biomonitoring studies to further elucidate its usefulness and biological significance for neurological impairments.